PERANCANGAN SISTEM INFORMASI PEMESANAN KAMAR PADA HOTEL BERBASIS WEBSITE - Widodo, Andrian Eko; Abror, Dzulchan (CONTEN : Computer and Network Technology, 2023)
Abstrak Studi ini fokus pada perancangan dan implementasi sistem informasi booking room pada hotelier dengan tujuan membangun solusi yang efisien, handal, dan user-friendly. Sistem ini menggabungkan kemudahan penggunaan dengan aksesibilitas yang lebih luas, menghubungkan tamu dengan berbagai pilihan hotel, fasilitas, dan harga yang sesuai dengan preferensi mereka. Melalui sistem ini, tamu hotel dapat menelusuri informasi penting seperti jenis kamar yang tersedia, fasilitas yang ditawarkan, lokasi hotel, foto-foto kamar dan fasilitas, serta ulasan dari tamu sebelumnya. Selain memberikan manfaat bagi tamu hotel, sistem informasi booking room juga memberikan manfaat yang signifikan bagi manajemen hotel. Dengan adanya sistem ini, manajemen dapat mengelola inventaris kamar secara efisien, menjadikan proses reservasi lebih teratur, dan meningkatkan efisiensi operasional secara keseluruhan. Data yang terkumpul melalui sistem informasi ini juga dapat memberikan wawasan berharga dalam mengoptimalkan strategi pemasaran, mengidentifikasi tren permintaan, dan meningkatkan kepuasan tamu. Namun, pembuatan dan implementasi sistem informasi booking room bukanlah tugas yang mudah. Setiap hotel memiliki kebutuhan dan tantangan operasional yang unik, sehingga sistem ini harus dirancang dan dikembangkan dengan hati-hati, mempertimbangkan semua faktor tersebut. Dengan studi ini, diharapkan dapat memberikan solusi yang efisien, handal, dan user-friendly untuk membantu hotel memaksimalkan layanan mereka dan mencapai tingkat kepuasan pelanggan yang lebih tinggi. Kata kunci: Sistem Informasi Booking Room, Industri Perhotelan, Pemesanan Kamar Hotel Abstract This research aims to design and implement a room booking information system in the hospitality industry. In the ever-evolving digital era, technological transformation has had a significant impact on the hospitality sector. The process of booking hotel rooms has evolved from the use of telephone or direct visits to hotel locations to easy and fast online booking through information systems. The hotel room booking information system is an innovative platform that makes it easy for hotel guests to search, select, and book rooms in an efficient and effective way.This study focuses on the design and implementation of a hotelier room booking information system with the aim of building an efficient, reliable, and user-friendly solution. The system combines ease of use with wider accessibility, connecting guests with a wide selection of hotels, facilities, and prices that match their preferences. Through this system, hotel guests can browse important information such as the types of rooms available, facilities offered, hotel location, photos of rooms and facilities, and reviews from previous guests. In addition to providing benefits for hotel guests, the room booking information system also provides significant benefits for hotel management. With this system, management can manage room inventory efficiently, make the reservation process more organized, and improve overall operational efficiency. The data collected through this information system can also provide valuable insights in optimizing marketing strategies, identifying demand trends, and improving guest satisfaction.However, the creation and implementation of a room booking information system is not an easy task. Each hotel has unique operational needs and challenges, so this system must be carefully designed and developed, considering all these factors. With this study, it is expected to provide an efficient, reliable, and user-friendly solution to help hotels maximize their services and achieve higher levels of customer satisfaction. Keywords: Booking Room Information System, Hotel Industry, Hotel Room Reservation